(untitled) (Web of Teachers: Inderscience Research, 2026)
Throughout the course of human history, there exists a fundamental connection between thought and reality. Specifically, the nexus of this relationship lies in social practices that shape the logical frameworks and principles of thought. Individuals acquire knowledge about their surroundings through emotional cognitive processes, yet this has occasionally resulted in misconceptions, such as the belief in a flat Earth or the geocentric model of the solar system. These misconceptions often led to skepticism towards sensory information, with rationalists downplaying the significance of sensory organs in cognition and emphasizing the primacy of thought. Conversely, proponents of empiricism in philosophy contested this perspective, arguing that excessive reliance on thought can introduce errors in understanding.